Management of Displaced Supracondylar Fracture of Late Presentation in Children by Open Reduction and Internal Fixation (KYAMC Journal, 2017)
Background: In late presentation of cases there is dilemma whether to wait for osteotomy later or do open reduction on arrival. The purpose of this prospective multicentric study is to evaluate the functional outcome of open reduction and internal fixation (ORIF) with crossed Kirschner wires fixation and early joint motion in the late presentation of supracondylar fractures in children.Methods: A total of 21 children, with an average delay of 22.5 days, with displaced type III Gartland supracondylar fracture, were treated by ORIF with crossed Kirschner wires fixation and early joint motion. Average follow-up was 12 months.Results: Flynn's criteria were used to evaluate the outcome. All of them had more functional range of motion of the injured elbow than the published reports.Conclusions: Most of the surgeons in the developing world prefer ORIF for optimal results. Thus it appears to be justifiable to go for ORIF with K-wires even in the late presentation of supracondylar fractures. The overall results are encouraging. However, the small number of cases and lack of control group are the limitations of this study. The study is ongoing and so the full report with more cases will be presented later.KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 745-749